2015
DOI: 10.5527/wjn.v4.i1.31
|View full text |Cite
|
Sign up to set email alerts
|

Complement activation in progressive renal disease

Abstract: ritis, thrombotic microangiopathies and transplant reje ction. In this review we discuss current evidence that complement activation contributes to progression of CKD, how complement could cause renal inflammation and whether complement inhibition would slow progression of renal disease. Core tip: Complement activation occurs in progressive chronic kidney disease and may contribute to the chronic inflammation that is characteristically found in the kidney. It is therefore possible that inhibiting complement ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 91 publications
2
50
0
Order By: Relevance
“…The production of complement‐activating microparticles might trigger acute inflammatory diseases (such as atypical hemolytic uremic syndrome) in susceptible patients, and the continuous production of complement‐activating microparticles might also be an important cause of chronic inflammation in CKD. As such, complement activation has been proposed to play a role in CKD 30. Consistent with this hypothesis, we previously observed elevated levels of complement activation fragments in a small number of patients with CKD 31…”
Section: Introductionsupporting
confidence: 80%
“…The production of complement‐activating microparticles might trigger acute inflammatory diseases (such as atypical hemolytic uremic syndrome) in susceptible patients, and the continuous production of complement‐activating microparticles might also be an important cause of chronic inflammation in CKD. As such, complement activation has been proposed to play a role in CKD 30. Consistent with this hypothesis, we previously observed elevated levels of complement activation fragments in a small number of patients with CKD 31…”
Section: Introductionsupporting
confidence: 80%
“…Complement activation occurs in the kidney during the progression of a broad range of renal diseases and could contribute to the inflammatory environment in which fibrosis occurs (31). A recent report indicated that local activation of the complement system mediates renal injury in diabetic nephropathy, wherein complement C3 reactivity in tubules leads to broader renal activation of the complement system, which is sustained by suppression of complement regulators, and contributes to renal inflammation, impaired function, and fibrosis (32).…”
Section: Discussionmentioning
confidence: 99%
“…5 In addition, recent evidence points to complement activation as a significant factor in the progression of chronic native kidney disease, which is likely to have generic application relevant to the transplanted organ. 6 How these observations will be translated to the clinical realm remains to be identified, as any intervention will need to weigh its effect on organ injury and rejection with dampening the antimicrobial functions of the complement system, such as opsonisation, cell lysis, and recruitment of neutrophils and other inflammatory cells. 7 It is our belief that therapeutic strategies can be designed to specifically target the key initiators of complement activation at the relevant location, such as complement-binding anti-HLA antibodies in the vascular compartment or the initiator(s) of local complement activation in the extravascular compartment of the allograft itself.…”
mentioning
confidence: 99%